NARINGIN'S POTENTIAL AS A HEPATITIS B VIRUS REPLICATION INHIBITOR: AN IN-SILICO STUDY OF SECONDARY METABOLITE COMPOUND - Muhammad Khalil; Muh. Nur Akbar; Ardiyas Robi Saputra; Subhan Hadi Kusuma (Universitas Muhammadiyah Magelang, 2023)
Naringin is a secondary metabolite compound of the flavonoid group which is generally found in plants that are consumed and traditionally used as medicine. The aim of this study was to examine the potential of naringin as a candidate for hepatitis B virus replication inhibitor using an in-silico approach. This research uses exploratory descriptive method with molecular docking analysis was carried out using the blind docking technique. The 3D structures of naringin and reference ligands were collected from the PubChem database, and the 3D structures of target proteins were collected from the PDB database. The target protein used is the hepatitis B virus capsid protein with PDB ID: 5GMZ. Docking analysis was performed using AutoDock Vina which is integrated into PyRx. Docking results were visualized using the PyMol software and Biovia Discovery Studio 2019. The results of the analysis showed that the binding affinity of all simulation models between naringin and the HBV capsid protein ranged from -7.1 to -7.9 kcal/mol. The binding site formed between naringin and the receptor corresponds to the reference ligand, involving the same 12 amino acid residues, namely PHE 23, PRO 25, LEU 30, THR 33, TRP 102, ILE 105, SER 106, PHE 110, TYR 118, ILE 139, LEU 140, and SER 141. Based on these results, it can be concluded that the naringin compound has the same bioactivity as the reference ligand in inhibiting viral replication, so that naringin has the potential as a candidate for hepatitis B virus replication inhibitor